Alkaline bentonite-based composite material for pellets as well as preparation method and application of alkaline bentonite-based composite material

By purified and modified alkaline bentonite matrix composites, the problems of lowering pellet ore grade and increasing smelting slag caused by traditional bentonite are solved, and the effect of reducing soil injection and increasing iron ore powder utilization is achieved.

CN119162456AActive Publication Date: 2024-12-20LIAONING GOLD STANDARD QUALITY RES INST CO LTD

Patent Information

Application Number
CN202411671101.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Traditional bentonite, as a pellet ore binder, has high silicon and aluminum content, resulting in a decrease in the pellet ore grade, an increase in the amount of blast furnace smelting slag, a decrease in the utilization coefficient of blast furnace, and an increase in the coke ratio.

Method used

The alkaline bentonite-based composite material is used to purify natural bentonite by water washing and sedimentation and high-speed centrifugation, and the artificial sodium bentonite is modified using organic modifiers with hydroxyl and carboxyl groups, and calcium-magnesium solvents, co-solvents and explosion-proof agents are added. An alkaline bentonite-based composite material with improved alkalinity of pellet ore was prepared for pelletizing.

Benefits of technology

It significantly reduces the amount of soil poured by the pellet ore, reduces the emission of smelting slag, increases the utilization rate of iron ore powder, achieves the goal of "improving iron and reducing silicon", improves production efficiency and reduces coke consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162456A_ABST
    Figure CN119162456A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of binders for metallurgy, in particular to an alkaline bentonite-based composite material for pellets as well as a preparation method and application of the alkaline bentonite-based composite material. The composite material is prepared from the following components in percentage by mass: 50 to 60 percent of artificial sodium bentonite, 30 to 40 percent of calcium magnesium solvent, 5 to 15 percent of organic modifier, 0.2 to 0.3 percent of cosolvent and 0.2 to 0.3 percent of antiknock agent. Natural bentonite is purified through a washing sedimentation and high-speed centrifugation method, artificial sodium bentonite is modified through a modification material, after separation, on the basis of separation and ultrasonic treatment, a calcium magnesium solvent is added to adjust the alkalinity of pellets, and therefore the alkaline bentonite-based composite material is prepared. According to the prepared alkaline bentonite-based composite material, the alkalinity of pellets is effectively improved, the bonding effect of the pellets is improved, and the soil feeding amount of the pellets is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metallurgical binders, and in particular to an alkaline bentonite-based composite material for pelletizing, and a preparation method and application thereof. Background Art

[0002] Pellets are considered to be high-quality materials necessary for optimizing the structure of blast furnace materials due to their good metallurgical properties and the advantages of improving the permeability of blast furnace material columns. They play a vital role in promoting capacity improvement and energy conservation and emission reduction in the smelting process of the steel industry. Bentonite, as the most widely used binder in pellet production, is an indispensable auxiliary material in pellet production and sintering production in the steel industry. Since almost all pellet plants in China use high-ratio bentonite as a binder, bentonite almost always remains in the pellets, thus reducing the grade of the pellets. Moreover, for every 1 percentage point increase in the bentonite content, the grade of the pellets will decrease by 0.66%, and the SiO2 content of the corresponding finished ore will also increase significantly.

[0003] High-quality bentonite-based composite materials have the characteristics of energy saving and consumption reduction, increased output, reduced slag discharge, and reduced pollution in pelletizing and sintering production applications, which can produce good economic, social and environmental benefits. They not only increase the added value of traditional bentonite resources, realize the optimization and upgrading of industrial structure, but also improve the grade of pellet ore and the rational use of iron ore concentrate, thereby promoting energy conservation and emission reduction in the industry and improving the overall benefits of enterprises. With the green and low-carbon transformation of the steel industry, the use of new bentonite-based composite materials to replace traditional bentonite has become an inevitable trend for improving the quality and reducing consumption of iron ore pelletizing processes. Summary of the invention

[0004] Aiming at the problems of high silicon and aluminum content, large dosage, reduced pellet grade, increased blast furnace smelting slag, reduced blast furnace utilization coefficient, and increased coke ratio when using ordinary bentonite as a pellet binder, the present invention provides an alkaline bentonite-based composite material for pellets and its preparation method and application, which greatly reduces the amount of soil added to the pellets, reduces the amount of slag discharge, increases the amount of iron ore powder added, improves production efficiency, and reduces coke consumption. Moreover, the reduction in the amount of soil added also reduces the content of silicon dioxide in the iron ore pellets, thereby improving the grade of the iron ore and achieving the goal of "increasing iron and reducing silicon".

[0005] In order to achieve the above object, the technical solution of the present invention is as follows: On one hand, the present invention provides a method for preparing an alkaline bentonite-based composite material, wherein the composite material is composed of the following components by weight: 50-60% artificial sodium bentonite, 30-40% calcium magnesium solvent, 5-15% organic modifier, 0.2-0.3% cosolvent, and 0.2-0.3% explosion-proof agent; The method comprises the following steps: (1) crushing the calcium-based bentonite ore, passing it through a 100-mesh sieve, adding water and stirring evenly to obtain a bentonite slurry, allowing it to stand, taking the upper suspension for centrifugal treatment, and taking a sediment; (2) Add water to the sediment 1 and stir evenly, let it stand, take the upper suspension and centrifuge it, repeat this step 1-2 times to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to obtain bentonite slurry 2, adding sodium carbonate, stirring at room temperature for 10-20 minutes, and then centrifuging to obtain sediment 3 to obtain artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) is passed through a 325-mesh sieve, water is added and stirred evenly to obtain bentonite slurry (3), an organic modifier is added, wherein the organic modifier is composed of quaternary ammonium salt organic matter and humic acid, and the mass ratio of the quaternary ammonium salt organic matter to the humic acid is 4:1, and the pH is adjusted to 8, stirred at 50-70° C. for 4-5 hours, and then centrifuged to obtain a sediment (4) to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 680-750°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) The organic modified bentonite obtained in step (4) is added with water and stirred evenly to obtain bentonite slurry 4, the bentonite slurry 4 is subjected to ultrasonic treatment, and then centrifugal treatment is performed, the sediment 4 is dried, ground into powder, and then a calcium magnesium solvent, a co-solvent, and an explosion-proof agent are added and evenly mixed to obtain an alkaline bentonite-based composite material.

[0006] In the above technical solution, further, in the step (1), the concentration of the bentonite slurry 1 is 10-30wt%; if the slurry concentration is lower than 10%, the amount of water will increase and it will be inconvenient for subsequent purification; if it is higher than 30%, it will cause uneven dispersion of the bentonite and thus insufficient purification; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min; The standing time is 5-10 minutes.

[0007] In the above technical solution, further, in the step (2), the centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min; The standing time is 5-10 minutes.

[0008] In the above technical solution, further, in the step (3), the concentration of the second bentonite slurry is 10-30wt%; The amount of sodium carbonate added is 3% of the mass of bentonite slurry 2; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min.

[0009] In the above technical solution, further, in the step (4), the centrifugal speed is 4000-5000 r / min, and the centrifugal time is 5-10 min.

[0010] In the above technical solution, further, in the step (6), the concentration of the bentonite slurry 4 is 10-30wt%; The ultrasonic power is 0.8-1.2KW, and the ultrasonic time is 0.5-1h; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min; The drying temperature is 105-120℃ and the drying time is 2-4h.

[0011] Another aspect of the present invention provides an alkaline bentonite-based composite material obtained by the above preparation method.

[0012] The present invention also provides an application of the alkaline bentonite-based composite material in the preparation of pelletized ore, wherein the composite material is added to iron ore powder for pelletizing, and the addition amount of the composite material accounts for 1% of the mass of the iron ore powder.

[0013] The beneficial effects of the present invention are: 1. The present invention purifies natural bentonite by water washing, sedimentation and high-speed centrifugation, and then uses a modified material with a heterocyclic structure having both hydroxyl and carboxyl groups and other small amounts of amide groups to modify artificial sodium bentonite. After separation, a certain amount of calcium and magnesium solvent is added thereto on the basis of sorting and ultrasonic treatment to adjust the alkalinity of the pelletized ore, and then a co-solvent and an explosion-proof agent are added in corresponding proportions and uniformly mixed to prepare an alkaline bentonite-based composite material.

[0014] 2. The alkaline bentonite-based composite material prepared by the present invention effectively increases the alkalinity of the pellets, improves the bonding effect of the pellets, and greatly reduces the amount of soil added to the pellets, so that the amount of soil added is adjusted between 0.5-0.6%, which is 2-4 times lower than that using traditional artificial sodium bentonite, and reduces the emission of smelting slag.

[0015] 3. In the iron-making process, the improvement of the iron grade of pellet ore not only promotes the maximum utilization of iron ore concentrate, but also has important significance for the promotion of energy conservation and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The process flow chart of the preparation method of the alkaline bentonite-based composite material of the present invention; Figure 2 This is the SEM image of the organic modified bentonite prepared in Example 1; Figure 3 This is the XRD pattern of the organic modified bentonite prepared in Example 1. DETAILED DESCRIPTION

[0017] The following examples may enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0018] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0019] Example 1 The composite material of this embodiment is composed of the following components by weight: 55% artificial sodium bentonite, 34.5% calcium magnesium solvent, 10% organic modifier, 0.25% co-solvent, and 0.25% explosion-proof agent. The preparation method comprises the following steps: (1) The calcium-based bentonite ore was crushed by a crusher, passed through a 100-mesh sieve, and mixed with water to prepare a 10 wt% bentonite slurry. The slurry was allowed to stand for 10 min, and the upper suspension was centrifuged at 5000 r / min for 5 min to obtain a sediment. (2) Add water to the sediment 1 and stir evenly, let it stand for 5 minutes, take the upper suspension and centrifuge it at 5000r / min for 5 minutes, repeat this step twice to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to prepare a 30 wt% bentonite slurry 2, adding sodium carbonate accounting for 3% of the mass of the bentonite slurry 2, stirring at 500 r / min for 20 min at room temperature, and then centrifuging at 5000 r / min for 5 min, taking the sediment 3, and obtaining artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) was passed through a 325-mesh sieve, water was added and stirred evenly, a 30 wt% bentonite slurry (3) was prepared, CTAB and humic acid were added, and the pH was adjusted to 8, the mixture was stirred at 50° C. for 5 h, and then centrifuged at 5000 r / min for 5 min, and the sediment (4) was collected to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 700°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) The organic modified bentonite obtained in step (4) is mixed with water and stirred to prepare a 30 wt% bentonite slurry 4. The bentonite slurry 4 is subjected to ultrasonic treatment at an ultrasonic power of 1 kW and an ultrasonic time of 0.5 h. The slurry is then centrifuged at 5000 r / min for 5 min. The sediment 4 is dried at 105° C. for 4 h, ground into powder, and then a calcium magnesium solvent, a co-solvent and an explosion-proof agent are added and mixed uniformly to obtain an alkaline bentonite-based composite material.

[0020] Example 2 The composite material of this embodiment is composed of the following components by weight: 50% artificial sodium bentonite, 34.5% calcium magnesium solvent, 15% organic modifier, 0.25% co-solvent, and 0.25% explosion-proof agent. The preparation method comprises the following steps: (1) The calcium-based bentonite ore was crushed by a crusher, passed through a 100-mesh sieve, and mixed with water to prepare a 30 wt% bentonite slurry. The slurry was allowed to stand for 10 min, and the upper suspension was centrifuged at 5000 r / min for 5 min to obtain a sediment. (2) Add water to the sediment 1 and stir evenly, let it stand for 10 minutes, take the upper suspension and centrifuge it at 5000r / min for 5 minutes, repeat this step twice to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to prepare a 30 wt% bentonite slurry 2, adding sodium carbonate accounting for 3% of the mass of the bentonite slurry 2, stirring at 500 r / min for 20 min at room temperature, and then centrifuging at 5000 r / min for 5 min, taking the sediment 3, and obtaining artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) was passed through a 325-mesh sieve, water was added and stirred evenly, a 30 wt% bentonite slurry (3) was prepared, CTAB and humic acid were added, and the pH was adjusted to 8, the mixture was stirred at 50° C. for 5 h, and then centrifuged at 5000 r / min for 5 min, and the sediment (4) was collected to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 700°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) The organic modified bentonite obtained in step (4) is mixed with water and stirred to prepare a 30 wt% bentonite slurry 4. The bentonite slurry 4 is subjected to ultrasonic treatment at an ultrasonic power of 1.2 kW and an ultrasonic time of 0.5 h. The slurry is then centrifuged at 5000 r / min for 5 min. The sediment 4 is dried at 105° C. for 4 h, ground into powder, and then a calcium magnesium solvent, a co-solvent and an explosion-proof agent are added and mixed uniformly to obtain an alkaline bentonite-based composite material.

[0021] Example 3 The composite material of this embodiment is composed of the following components by weight: 60% artificial sodium bentonite, 34.5% calcium magnesium solvent, 5% organic modifier, 0.25% co-solvent, and 0.25% explosion-proof agent. The preparation method comprises the following steps: (1) The calcium-based bentonite ore was crushed by a crusher, passed through a 100-mesh sieve, and mixed with water to prepare a 10 wt% bentonite slurry. The slurry was allowed to stand for 10 min, and the upper suspension was centrifuged at 5000 r / min for 5 min to obtain a sediment. (2) Add water to the sediment 1 and stir evenly, let it stand for 10 minutes, take the upper suspension and centrifuge it at 5000r / min for 5 minutes, repeat this step twice to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to prepare a 10 wt% bentonite slurry 2, adding sodium carbonate accounting for 3% of the mass of the bentonite slurry 2, stirring at 500 r / min for 20 min at room temperature, and then centrifuging at 5000 r / min for 5 min, taking the sediment 3, and obtaining artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) was passed through a 325-mesh sieve, water was added and stirred evenly, a 10 wt% bentonite slurry (3) was prepared, CTAB and humic acid were added, and the pH was adjusted to 8, the mixture was stirred at 50° C. for 5 h, and then centrifuged at 5000 r / min for 5 min, and the sediment (4) was collected to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 700°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) The organic modified bentonite obtained in step (4) is mixed with water and stirred to prepare a 30 wt% bentonite slurry 4. The bentonite slurry 4 is subjected to ultrasonic treatment at an ultrasonic power of 1.2 kW and an ultrasonic time of 0.5 h. The slurry is then centrifuged at 5000 r / min for 5 min. The sediment 4 is dried at 105° C. for 4 h, ground into powder, and then a calcium magnesium solvent, a co-solvent and an explosion-proof agent are added and mixed uniformly to obtain an alkaline bentonite-based composite material.

[0022] Example 4 The composite material of this embodiment is composed of the following components by mass: 55% bentonite, 34.5% calcium magnesium solvent, 10% organic modifier, 0.25% co-solvent, and 0.25% explosion-proof agent. The preparation method includes the following steps: (1) The calcium-based bentonite ore was crushed by a crusher, passed through a 100-mesh sieve, and mixed with water to prepare a 30 wt% bentonite slurry. The slurry was allowed to stand for 10 min, and the upper suspension was centrifuged at 4000 r / min for 10 min to obtain a sediment. (2) Add water to the sediment 1 and stir evenly, let it stand for 5 minutes, take the upper suspension and centrifuge it at 4000r / min for 10 minutes, repeat this step twice to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to prepare a 30 wt% bentonite slurry 2, adding sodium carbonate accounting for 3% of the mass of the bentonite slurry 2, stirring at 500 r / min for 20 min at room temperature, and then centrifuging at 4000 r / min for 10 min, taking the sediment 3, and obtaining artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) was passed through a 325-mesh sieve, water was added and stirred evenly, a 30 wt% bentonite slurry (3) was prepared, CTAB and humic acid were added, and the pH was adjusted to 8, the mixture was stirred at 70° C. for 4 h, and then centrifuged at 4000 r / min for 10 min, and the sediment (4) was collected to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 700°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) The organic modified bentonite obtained in step (4) is mixed with water to prepare a 30 wt% bentonite slurry 4, and the bentonite slurry 4 is subjected to ultrasonic treatment at an ultrasonic power of 1 kW and an ultrasonic time of 0.5 h. The slurry is then centrifuged at 4000 r / min for 10 min. The sediment 4 is dried at 120° C. for 2 h, ground into powder, and then a calcium magnesium solvent, a co-solvent, and an explosion-proof agent are added and mixed uniformly to obtain an alkaline bentonite-based composite material.

[0023] In the above embodiments, the cosolvent, explosion-proof agent, and quaternary ammonium salt organic matter are all made of conventional materials in the art. The cosolvent includes but is not limited to sodium pyrophosphate and sodium hexametaphosphate; the explosion-proof agent includes but is not limited to ammonium nitrate and sodium silicate; the quaternary ammonium salt organic matter includes but is not limited to hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide.

[0024] The composite materials of Examples 1-4 were used together with traditional artificial sodium bentonite to make pellets. The properties of the pellets are shown in Table 1.

[0025] Table 1 Analysis of pellet properties after pelletizing with different materials

[0026] like Figure 3 As shown in the figure, by comparing with the unmodified bentonite, the characteristic peak of the organic modified bentonite at around 5° is significantly weakened, which indicates that the organic matter has been inserted into the interlayer structure of the bentonite and the organic modification is quite significant. This is shown in the SEM image ( Figure 2 ) can also be seen on the particles with flaky substances, thus confirming that the bentonite has been organically modified.

[0027] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing an alkaline bentonite-based composite material, characterized in that: The composite material is composed of the following components by weight: 50-60% artificial sodium bentonite, 30-40% calcium magnesium solvent, 5-15% organic modifier, 0.2-0.3% co-solvent, and 0.2-0.3% explosion-proof agent; The method comprises the following steps: (1) crushing the calcium-based bentonite ore, passing it through a 100-mesh sieve, adding water and stirring evenly to obtain a bentonite slurry, allowing it to stand, taking the upper suspension for centrifugal treatment, and taking a sediment; (2) Add water to the sediment 1 and stir evenly, let it stand, take the upper suspension and centrifuge it, repeat this step 1-2 times to obtain sediment 2; (3) adding water to the sediment obtained in step (2) and stirring evenly to obtain bentonite slurry 2, adding sodium carbonate, stirring at room temperature for 10-20 minutes, and then centrifuging to obtain sediment 3 to obtain artificial sodium bentonite; (4) The artificial sodium bentonite obtained in step (3) is passed through a 325-mesh sieve, water is added and stirred evenly to obtain bentonite slurry (3), an organic modifier is added, wherein the organic modifier is composed of quaternary ammonium salt organic matter and humic acid, and the mass ratio of the quaternary ammonium salt organic matter to the humic acid is 4:1, and the pH is adjusted to 8, stirred at 50-70° C. for 4-5 hours, and then centrifuged to obtain a sediment (4) to obtain an organic modified bentonite; (5) Grinding the dolomite calcined at 680-750°C into powder and passing it through a 325-mesh sieve to obtain a calcium-magnesium solvent; (6) Add water to the organic modified bentonite obtained in step (4) and stir evenly to obtain bentonite slurry 4, subject the bentonite slurry 4 to ultrasonic treatment, and then subject it to centrifugal treatment, take the sediment 4, dry it, grind it into powder, and then add calcium magnesium solvent, co-solvent and explosion-proof agent, mix them evenly, and obtain an alkaline bentonite-based composite material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of bentonite slurry 1 is 10-30wt%; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min; The standing time is 5-10 minutes.

3. The preparation method according to claim 1, characterized in that: In the step (2), the centrifugal speed is 4000-5000 r / min, and the centrifugal time is 5-10 min; The standing time is 5-10 minutes.

4. The preparation method according to claim 1, characterized in that: In the step (3), the concentration of the second bentonite slurry is 10-30wt%; The amount of sodium carbonate added is 3% of the mass of bentonite slurry 2; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min.

5. The preparation method according to claim 1, characterized in that: In the step (4), the centrifugal speed is 4000-5000 r / min, and the centrifugal time is 5-10 min.

6. The preparation method according to claim 1, characterized in that: In the step (6), the concentration of the bentonite slurry 4 is 10-30wt%; The ultrasonic power is 0.8-1.2KW, and the ultrasonic time is 0.5-1h; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 5-10min; The drying temperature is 105-120℃ and the drying time is 2-4h.

7. An alkaline bentonite-based composite material obtained by the preparation method according to any one of claims 1 to 6.

8. An application of the alkaline bentonite-based composite material according to claim 7, characterized in that: The composite material is added to iron ore powder for pelletizing, and the added amount of the composite material accounts for 1% of the mass of the iron ore powder.

Citation Information

Patent Citations

  • Composite Na-based bentonite and preparation method thereof

    CN101519210A

  • Magnesium-containing compounded additive and preparation method thereof

    CN104805279A

  • Preparation method for humic acid modified bentonite for iron ore pellets and application of humic acid modified bentonite

    CN105087912A

  • Method for modifying calcium bentonite

    CN111470514A

  • Method for obtaining organophilic powdered bentonite

    RU2665425C1

Cited By

  • Two-section type variable-binder and variable-rotating-speed pelletizing method

    CN120060633A